Articular Cartilage Repair With Magnetic Mesenchymal Stem Cells. (June 2013) - Kamei, Goki; Kobayashi, Takaaki; Ohkawa, Shingo; Kongcharoensombat, Wirat; Adachi, Nobuo; Takazawa, Kobun; Shibuya, Hayatoshi; Deie, Masataka; Hattori, Koji; Goldberg, Jeffrey L.; Ochi, Mitsuo
Background: Cell therapies are hampered by the difficulty of delivering cells to and retaining them in target tissues long enough to repair or regenerate local tissues. Hypothesis: Magnetic-assisted delivery of magnetically labeled mesenchymal stem cells (m-MSCs) would be rapid, allowing for chondrogenic differentiation and functional joint repair without replacement. Study Design: Controlled laboratory study. Methods: Sixteen mini-pigs aged 6 to 7 months were used. A full-thickness cartilage defect was created in the center of the patella with a cylindrical punch (diameter, 6 mm). At 4 weeks after creation of the cartilage defects, the animals were divided into 3 treatment groups: In the M group, m-MSCs (5 × 10 6 cells) were injected and accumulated to the cartilage defect using an external magnetic force (1.5 T) for 10 minutes; in the G group, the patella was faced upward, filled with MSCs (5 × 10 6 cells), and held for 10 minutes; and in the C group, only phosphate-buffered saline was injected. The regenerated cartilage was evaluated in 5 knees in each of the 3 groups by arthroscopic surgery at 6 and 12 weeks and histological and ultrasound evaluation at 12 and 24 weeks. Results: The mean arthroscopic scores at 6 weeks were 10.4 ± 1.10 in the M group, 8.8 ± 0.84 in the G group, and 7.4 ± 0.89 in the C group. There was a statistically significant difference between the M group and the other 2 groups. The mean arthroscopic scores at 12 weeks were 12.8 ± 1.30 (M group), 10.5 ± 1.30 (G group), and 9.5 ± 0.58 (C group), with a statistically significant difference between the M and C groups. The mean histological scores using the Wakitani scoring system at 12 weeks were 2.8 ± 0.96 (M group), 5.4 ± 0.55 (G group), and 6.0 ± 2.20 (C group), and the mean histological scores at 24 weeks were 2.4 ± 1.50 (M group), 3.5 ± 0.56 (G group), and 5.3 ± 1.50 (C group). The mean histological scores at 12 weeks were significantly better in the M group than in the other groups, and the M group maintained a significantly better histological score than did the C group at 24 weeks. Conclusion: The m-MSCs had no adverse effect on chondrogenic differentiation, and m-MSCs delivered by magnetic field application repaired cartilage defects. Clinical Relevance: The clinical application of this novel stem cell delivery system is a potential therapeutic option for treating cartilage defects and may be more applicable throughout the body than traditional methods.